High BMI-attributed diabetic kidney disease in China versus globally, 1990–2021, with projections to 2045: Divergent trends and an accelerating burden - Luyao Jiang; Jinkang Jia; Tianxi Chen; Linlin Xu; Miaojun Shi (PLoS ONE, 2025)
Objective To analyze the accelerating burden and unique trends of diabetic kidney disease (DKD) attributable to high body mass index (BMI) in China from 1990 to 2021, contextualized against global patterns. Methods Relevant data were extracted from the Global Burden of Disease 2021 study. Trends in disease burden were analyzed using a joinpoint regression model. The disease burdens during the period of 2022–2045 were forecasted using the NORDPRED model. Results From 1990 to 2021, the absolute burden of high BMI-attributable DKD increased dramatically in China, with the number of deaths surging by 355%. While global trends also rose, China exhibited unique characteristics: a disproportionately high burden was observed in men aged 85 and above, a pattern not seen globally. Spatiotemporal analysis revealed China progressed to a higher global burden stratum over the three decades. Projections indicate the number of deaths and DALYs in China will continue to rise steeply through 2045. Conclusion The burden of DKD attributable to high BMI has increased at an alarming rate in China, with distinct demographic vulnerabilities. These findings underscore the urgent need for targeted national public health interventions to mitigate this formidable challenge.